UPAYA PEMERINTAH DAERAH DALAM PEMBANGUNAN KEPARIWISATAAN FESTIVAL PACU JALUR DI KABUPATEN KUANTAN SINGINGI TAHUN 2016-2017 - Desi Hardianti; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Tourism is one of the new industriest that can provide faster economic growth in terms of employment, income, living standards, and the effectiveness of other industrial sectors. The development of tourism in a region will bring many benefits for the society, namely economically, socially, and culture. Therefore, researchers want to see the efforts of local governments in the development of tourism Pacu Jalur in Kuantan Singingi regency in 2016-2017.This study aims to (1) Describe the effort of local governments in the development of tourism Pacu Jalur in Kuantan Singingi regency in 2016-2017, (2) Describe the inhibiting factors of local government in the developments of tourism Pacu Jalur in Kuantan Singingi regency 2016-2017. This research was conducted in Kuantan Singingi regency. Data collection technique is done by qualitative data analysis.The results concluded that the efforts of local governments in the development of tourism Pacu Jalur festival include development in the field of tourism industry, tourism destinations, tourism marketing and tourism institutions. The development of Pacu Jalur tourism is influenced by internal factors and external factors. Internal factor such as budget constraints, there are no local regulations directly related to Pacu Jalur, the lack of local government efforts to increase cooperation with private parties, and the lack of inventory data related to tourism development. External factors is include the lack of involvement of the company in the succes of the Pacu Jalur festival, the lack of public participation to engage in tourism development, and the tourism industry that is not orientedtoward the long term.Keyword: Local Government, Tourism Development, Pacu Jalur